Opportunity knocks: the intersection between schools, their teachers and external providers of physical education and school sport. Issue 2 (3rd March 2020) - Bowles, Richard; O'Sullivan, Mary
ABSTRACT: Recent studies suggest school communities accept the goods and services of external providers uncritically. Considering the pivotal role played by teachers in curriculum and policy enactment, this paper explores how and why teachers in Ireland advocate for, and engage with, the services and resources of one particular external provider, the Gaelic Athletic Association (GAA). This paper draws upon data generated from a purposive sample of teachers and external coaches who were involved in the provision of Gaelic games in primary schools. Semi-structured interviews were conducted with teachers and coaches, and policy documents were examined in order to gain a better understanding of the external provision provided by the GAA. The data were subsequently analysed thematically. Our findings suggest that teachers who promote Gaelic games within the core and extracurricular PE and sport programmes consider these games crucial to the development of children's sporting and cultural identity.